1994
DOI: 10.1111/j.1365-246x.1994.tb04002.x
|View full text |Cite
|
Sign up to set email alerts
|

An example of lateral-inhomogeneity effects on seismic traveltimes in a zero-offset VSP experiment

Abstract: S U M M A R Y 2-D random media with ellipsoidal autocorrelation functions are used to point out the effects of lateral inhomogeneities on zero-offset VSP data. The ellipsoidal autocorrelation functions allow the characterization of lateral and vertical inhomogeneities by two independent scaling factors a and b in the two Cartesian directions; a for lateral inhomogeneities and b for vertical inhomogeneities. Thus we can describe 2-D media by taking non-zero finite values of a and b, or l-D media by extending to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

1996
1996
2018
2018

Publication Types

Select...
2
1
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 9 publications
0
2
0
Order By: Relevance
“…When the noise correlation in the measurements is considerable, the correlation peak can be substantially distorted, resulting in imprecise and even biased estimation of the time delay. The synthetic data computed by Ikelle et al (1993) and Ikelle and Yung (1994) in their studies of wave propagation through random media provide a good example of data with considerable noise correlation. In picking the arrival times in this data set, we found that the crosscorrelation technique suffers both from the severely restricted signal bandwidth and from the presence of coda.…”
Section: Introductionmentioning
confidence: 99%
“…When the noise correlation in the measurements is considerable, the correlation peak can be substantially distorted, resulting in imprecise and even biased estimation of the time delay. The synthetic data computed by Ikelle et al (1993) and Ikelle and Yung (1994) in their studies of wave propagation through random media provide a good example of data with considerable noise correlation. In picking the arrival times in this data set, we found that the crosscorrelation technique suffers both from the severely restricted signal bandwidth and from the presence of coda.…”
Section: Introductionmentioning
confidence: 99%
“…In a randomly inhomogeneous medium characterized by homogeneous statistics (such a medium is said to be stationary), the phase velocity of the direct arrivals differs from the averaged velocity or from the inverse averaged slowness. Recently this phenomenon, termed 'velocity shift', has been considered by Miiller, Roth & Korn (1992), Roth, Miiller & Snieder (1993), van Avendonk & Snieder (1994) and Ikelle & Yung (1994).…”
Section: Introductionmentioning
confidence: 99%